The Role of Firm Size: Board Characteristics and Sustainability Reporting - Devi Nurdianta; Nanik Kustiningsih; Sri Rahayu (INVENTORY: JURNAL AKUNTANSI, 2026)
The strategic role of gender diversity and board size can ensure that sustainability information is prepared accurately, transparently, and in accordance with stakeholder needs, which can increase the credibility of sustainability reporting and also increase company assets, which are one of the factors attracting investor interest. This study aims to empirically test the effect of board characteristics indicated by gender diversity and board size on sustainability reporting, moderated by firm size. This study used a population of 516 non-cyclical sector companies listed on the Indonesia Stock Exchange in 2021-2024. After selecting the sample, 427 companies were used in this study. The study was tested using Process Macro v4.2 by Andre F. Hayes. The results showed that gender diversity had no effect on sustainability reporting, board size did affect sustainability reporting, firm size could not moderate the effect of gender diversity on sustainability reporting, and firm size could moderate the effect of board size on sustainability reporting.